Hazard mapping of Sindhu Khola watershed, Sindupalchowk, Nepal - Poudyal, Chandra Prakash (Kathmandu University Journal of Science Engineering and Technology, 2013)
The aim of present study is to produce landslide susceptibility map of Sindhu Khola watershed, Sindhupalchok, Kavre, Nepal, using Geographic Information System (GIS) by means of frequency ratio. The ArcView was used as primary software for the management of spatial data. Landslide locations were identified during the field visit. There are altogether seven different factors such as topographic slope, aspect, distance from drainage and so on, and their respective relations with the occurrence of landslides in the study area were analyzed. These factors were used to produce landslide susceptibility map using frequency ratio method. The frequency ratio suggests that distance near to drainage and slope angle higher than 30° are main factor contributing landslide occurrences. To assess the performance of the produced susceptibility map, the area under curve (AUC) is drawn. The AUC value of the produced landslide susceptibility map has been obtained as 79.65%. According to the results of the AUC evaluation, the produced map has exhibited a satisfactory performance.